1984
DOI: 10.1039/p29840001937
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the oxidation of alcohols and aldehydes with peroxydisulphate ion

Abstract: The kinetics of the reactions of peroxydisulphate with alcohols (methanol, ethanol, propan-1 -01, propan-2-01, and butanol) and with acetaldehyde have been studied. Their radical-chain behaviour has been established. Using a radical-scavenger method it has been shown that the chain-initiating step is the monomolecular homolysis of the peroxydisulphate anion. The 'limiting' concentration of the reducing agents, the mean kinetic chain length, and the overall energy of activation have been determined. The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…In the absence of O 2 , it is possible that HCHD radical was oxidized by S 2 O 8 2− to generate phenol (Reaction 13) and the ring-cleavage product (Reaction 14) at different ratios than those observed in the presence of O 2 . 34,52 Such a process would serve as a chain propagation reaction, producing one mole of SO 4 • for every mole of S 2 O 8 2− decomposed (Reactions 13-14 in Scheme 2). In the goethite-activated persulfate system, the concentration of the unknown compound was approximately 10 times higher in the N 2 -purged solution ([O 2 ]=3 μM) than that in O 2 -supersaturated solution ([O 2 ]=410 μM) after 5 days of reaction (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the absence of O 2 , it is possible that HCHD radical was oxidized by S 2 O 8 2− to generate phenol (Reaction 13) and the ring-cleavage product (Reaction 14) at different ratios than those observed in the presence of O 2 . 34,52 Such a process would serve as a chain propagation reaction, producing one mole of SO 4 • for every mole of S 2 O 8 2− decomposed (Reactions 13-14 in Scheme 2). In the goethite-activated persulfate system, the concentration of the unknown compound was approximately 10 times higher in the N 2 -purged solution ([O 2 ]=3 μM) than that in O 2 -supersaturated solution ([O 2 ]=410 μM) after 5 days of reaction (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The N 2 -purged solutions (i.e., [O 2 ] = 3 μM) resulted in the formation of phenol at concentrations that were approximately 30% of those observed under air-saturated conditions (i.e., [O 2 ] = 250 μM) or 10% of those observed under O 2 -supersaturated conditions (i.e., [O 2 ] = 410 μM). In the absence of O 2 , it is possible that HCHD radical was oxidized by S 2 O 8 2– to generate phenol (reaction 13) and the ring-cleavage product (reaction 14) at different ratios than those observed in the presence of O 2 . , Such a process would serve as a chain propagation reaction, producing one mole of SO 4 •– for every mole of S 2 O 8 2– decomposed (reactions 13–14 in Scheme ). In the goethite-activated persulfate system, the concentration of the unknown compound was approximately 10 times higher in the N 2 -purged solution ([O 2 ] = 3 μM) than that in O 2 -supersaturated solution ([O 2 ] = 410 μM) after 5 days of reaction (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior can also be explained by the radical chain reactions initiated by the reaction of SO 4 •– . It has been suggested that the one-electron oxidation of organic substrates by SO 4 •– produces an organo radical as an intermediate, which converts another PDS molecule into SO 4 •– , propagating the chain reactions (reactions and ). , …”
Section: Discussionmentioning
confidence: 99%